2014
DOI: 10.1590/0103-8478cr20131003
|View full text |Cite
|
Sign up to set email alerts
|

Expressão heteróloga da EMA-2 (equi merozoite antigen) de Theileria equi em Pichia pastoris com potencial utilização em imunobiológicos

Abstract: RESUMO A piroplasmose equina causada por Theileria equi acomete os equinos de forma endêmica no Brasil e em diversos outros países tropicais e subtropicais. Considerada uma das mais

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The method chosen to perform the serological evaluation of animals in this study was indirect ELISA. The protocol used had been already tested in a previous study and had showed 83.3% specificity and 90.9% sensitivity (Vianna et al 2014). Several variations of ELISA with different antigens have been successfully used in the diagnosis of and in studies with T. equi (Kumar et al 2013, El-Sayed et al 2015, Kumar et al 2015.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The method chosen to perform the serological evaluation of animals in this study was indirect ELISA. The protocol used had been already tested in a previous study and had showed 83.3% specificity and 90.9% sensitivity (Vianna et al 2014). Several variations of ELISA with different antigens have been successfully used in the diagnosis of and in studies with T. equi (Kumar et al 2013, El-Sayed et al 2015, Kumar et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the protein rEMA-2 in the vaccine formulation and as an antigen for the ELISA test is justifiable by the fact that EMA-2 is expressed in several stages of the protozoan life cycle. In addition, it is one of the first antigens to be recognized by the immune system through its expression on the membrane and cytoplasm of erythrocytes (Vianna et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations